(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
An overview of the role of vicariance-based and dispersal-based concepts in the development of global historical geography of plants is provided. Formation of evolutionary historical biogeography as a science and development of the dynamic evolutionary paradigm of biogeography became possible only after evolutionary works of CH. R. DARWIN and A. R. WALLACE. The names of DARWIN, WALLACE and J. D. HOOKER are closely tied to the formation of dispersal-based and vicariance-based approaches and paradigms. Basic directions, concepts and contemporary trends of development of global historical phytogeography are considered in a historical aspect. It is shown that basic concepts and principles underlying the modern historical phytogeographical analysis are (1) the evolutionary approach and incorporation of phylogeny into the taxonomic systems and phytogeographical schemes; (2) principle of actualism (uniformitarianism), with the use of paleobotanical data; (3) contemporary paleogeographic and paleogeological reconstructions and concept (global tectonics, glacial theory and others); (4) theory and the methods of vicariance biogeography; (5) theory and methods of dispersal biogeography; (6) testing hypotheses with the aid of molecular methods, etc.